Coupling sex and emotional expressiveness as determinants of marital intimacy among married couples - Jesuorobo, Wellington Omosefe; Igbineweka, Martins Noyosase (International Journal of Applied Guidance and Counseling, 2023)
The study examined coupling sex and emotional expressiveness and how they affect marital intimacy among married couples in Benin Metropolis of Edo state, Nigeria. Three hypotheses were raised to guide the study, while the descriptive correlational research design was adopted. Four hundred and fifty (450) spouses drawn from two churches (each from Pentecostal and Orthodox churches) in Benin metropolis were selected through simple sampling technique and convenience sampling method. The instrument used for the study was the researcher’s structured questionnaire titled Coupling Sex, Emotional Expressiveness and Marital Intimacy Questionnaire (C S E M I Q). Data collected were analysed using regression analysis. The findings of the study revealed that a combination of frequent coupling sex and emotional expressiveness had significant contribution to marital intimacy, while coupling sex and emotional expressiveness had some level of significant influence on marital intimacy. Based on the findings, it was recommended that Couples should sensitize regularly on the importance of regular and pleasurable sex and positive emotional expression in order to enhance healthy marital intimacy.